Killing them with Kindness: Negative Distributional Externalities of Increasing UI Benefits - John P. Haisken-DeNew; Matthias Vorell (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
Of the many labour market Hartz IV reforms that have been implemented in Germany since 2005, the role of short-term unemployment insurance has not received much attention. In this paper we examine distributional effects of labour earnings and unemployment benefits using simulated increases in unemployment insurance replacement rates or equivalently, increases in the net present value of benefit duration. Starting around an 18%-point increase in the replacement rate, there are significant negative labour supply effects, drawing those employed into unemployment shifting the mass of the earnings distribution to the left. At around a 25%-point increase in the replacement rate, the mass of the distribution shifts right again, as those receiving unemployment benefits simply enjoy an increased transfer. Thus, due to the substantial negative labour supply effects, German economic policy should avoid potentially increasing the UI benefit replacement rate (or equivalently, increasing the benefit duration) in the near future as a response to the worldwide economic crisis.
Keywords: J65; D31; J22; 330; Unemployment; income distribution; labour supply; Arbeitslosenversicherung; Hartz-Reform; Dauer; Wirtschaftspolitische Wirkungsanalyse; Verteilungswirkung; Arbeitsangebot; Arbeitslosigkeit; Deutschland